Patient selection and percutaneous technique of unprotected left main revascularization. Issue 4 (9th March 2018) - Testa, L.; Latib, A.; Bollati, M.; Bedogni, F.
Abstract: Increasing evidence suggests that percutaneous coronary intervention with newer generation drug‐eluting stents may be an acceptable alternative, or even preferred in selected cases to the surgical approach, in patients with left main disease. This review will discuss the anatomic factors, the clinical variables, and the procedural strategies to consider, including physiology assessment and imaging guidance, in order to optimize outcomes.